Maritime Energy Resources in Asia : Energy and Geopolitics - Schofield, Clive (NBR special report ;, 2011)
In this report a team of international scholars examines the energy and geopolitical drivers influencing the maritime jurisdictional disputes in the East China Sea, South China Sea, and Gulf of Thailand.